Morphometric analysis of the infraorbital groove, canal, and foramen on computed tomography scans of an Iranian population = Análisis morfométrico del surco, canal y foramen infraorbitario en tomografías computarizadas de una población iraní - Vaezi, Mojtaba; Karagah, Aida; Taghavi Damghani, Farnaz; Tofangchiha, Maryam; Alizadeh, Ahad (2025)
This study morphometrically assessed the infraorbital groove (IOG), canal (IOC) and foramen (IOF) on computed tomography (CT) scans of an Iranian population. This cross-sectional study evaluated the CT scans of 126 patients presenting to a hospital in Qazvin city, Iran during 2020-2022, who were selected by convenience sampling. An oral and maxillofacial surgeon and an oral and maxillofacial radiologist identified the relevant anatomical landmarks and the measurements were made by a trained senior dental student. Data were analyzed by independent t-test, and Pearson's correlation test (alpha=0.05). The mean IOC length was 9.86±1.34 mm, the mean IOG length was 12.78±1.57 mm, the mean IOC-IOG angle was 136.78±6.90 degrees, the mean IOC-vertical plane angle was 26.92±5.74 degrees, the mean IOC-horizontal plane angle was 58.54±6.18 degrees, the mean horizontal distance between the IOF and the sagittal plane passing through the supraorbital notch (SON) was 4.85±0.98 mm, the mean horizontal distance between the IOF and the sagittal plane passing through the midline was 23.04±2.90 mm, the mean vertical distance between the IOF and infraorbital rim (IOR) was 9.22±1.45 mm, the mean distance between the IOF and anterior nasal spine (ANS) was 27.63±10.99 mm, the mean angle between the IOF and ANS was 33.52±5.46 degrees, and the mean soft tissue thickness over the IOF was 10.60±2.04 mm. No significant difference was found in the parameters based on age (P>0.05). IOF-midline and IOF-IOR distances were significantly greater in males than females (P<0.05). No other significant differences were found based on gender (P>0.05). According to the results, the IOF-midline and IOF-IOR distances were significantly greater in Iranian males than females. The obtained results regarding the position of IOC, IOF, and IOG on CT scans of the Iranian study population can help maximize the success of related clinical procedures.
Este estudio evaluó morfométricamente el surco infraorbitario (IOG), el canal (IOC) y el foramen (IOF) en tomografías computarizadas (TC) de una población iraní. Este estudio transversal evaluó las tomografías computarizadas de 126 pacientes que se presentaron en un hospital en la ciudad de Qazvin, Irán, durante 2020-2022, que fueron seleccionados por muestreo de conveniencia. Un cirujano oral y maxilofacial y un radiólogo oral y maxilofacial identificaron los puntos de referencia anatómicos relevantes y las mediciones fueron realizadas por un estudiante de odontología capacitado. Los datos se analizaron mediante una prueba t independiente y una prueba de correlación de Pearson (alfa=0,05). La longitud media del IOF fue de 9,86±1,34 mm, la longitud media del IOG fue de 12,78±1,57 mm, el ángulo medio del IOF-IOG fue de 136,78±6,90 grados, el ángulo medio del plano vertical del IOF fue de 26,92±5,74 grados, el ángulo medio del plano horizontal del IOF fue de 58,54±6,18 grados, la distancia horizontal media entre el IOF y el plano sagital que pasa por la escotadura supraorbitaria (SON) fue de 4,85±0,98 mm, la distancia horizontal media entre el IOF y el plano sagital que pasa por la línea media fue de 23,04±2,90 mm, la distancia vertical media entre el IOF y el reborde infraorbitario (IOR) fue de 9,22±1,45 mm, la distancia media entre el IOF y la espina nasal anterior (ANS) fue de 27,63±10,99 mm, el ángulo medio entre el IOF y el ANS fue de 33,52±5,46 grados y el grosor medio del tejido blando sobre el IOF fue de 10,60±2,04 mm. No se encontraron diferencias significativas en los parámetros en función de la edad (P>0,05). Las distancias IOF-línea media y IOF-IOR fueron significativamente mayores en hombres que en mujeres (P<0,05). No se encontraron otras diferencias significativas en función del género (P>0,05). Según los resultados, las distancias IOF-línea media y OIF-IOR fueron significativamente mayores hombres iraníes...
En revista Odóvtos, Online First, 2025
Descripción basada en el contenido visto el 20 de marzo, 2025
También disponible en formato HTML y EPUB